The role of incentives and training programs on Job Satisfaction of Employees – An Empirical Study on Workers in the Arab Open University – - Al Otaibi, Fahdah Mihmas (Journal of Economic, Administrative and Legal Sciences, 2021)
This Study aimed to: identify extent of interesting in financial and moral incentives regulation and incentives regulation in Arab Open University , identify extent of interesting in humanistic value and electronic training of employees in Arab Open University, identify reality of job satisfaction for employees in Arab Open University, the analytical descriptive approach and study population is included all employees in Arab Open University in all their job levels, their number reached to (230) and the researcher is obtained (149) electronic response. The study revealed that study sample members are agree to some extent on degree of interesting in financial and moral incentives regulation and incentives regulation in Arab Open University where approval averages of study sample members is reached to (3.08), revealed that study sample members are agree to some extent on degree of interesting in humanistic value and electronic training of employees in Arab Open University where approval averages of study sample members is reached to (3.01) and revealed that study sample members have intermediate degree of job stratification where approval averages of study sample members reached to (2.85), the study recommended with necessity of work on adopting motivation system to comply with Arab Open University , providing the necessary moral for university relatives especially for the excellent employees and increasing financial incentives and allowances which is provided to the employees in university.